Pengaruh Profesionalisme Auditor terhadap Pertimbangan Tingkat Materialitas pada Kantor Akuntan Publik di Surabaya - Sofian, .; Lindrawati, . (Jurnal Akuntansi Kontemporer, 2011)
Financial report as a medium of communication required by the parties outside the company to base decision-making. So that financial statements can be a tool that is reliable and relevant for making a decision, financial statements need to be audited by an independent third party, in this case the external auditor. One of the auditor's responsibilities is to determine the materiality level consideration of client's financial statements, which is influenced by professionalism auditors. Therefore, this study aims to examine the influence of the professionalism auditors on materiality consideration. The research design was quantitative with the hypothesis. Data obtained directly from distributing questionnaires to the public accountant who worked in the office of the public accountant in Surabaya. Data analysis technique was using multiple linear regression models, testing the validity and reliability, test assurnptions classical, and hypothesis testing by t test. The analysis showed that the professionalism of auditors affect the level of materiality considerations. From the five dimensions of auditor professionalism, dedication to the profession and social obligations affect the level of material if, where dedication to the profession and social obligations have a positive influence, while not affecting auditor's consideration of materiality are autonomy, belief in self-regulation, and professional community affiliation. Keywords: external auditor, auditor's consideration of materiality, professionalism auditors.